Imam Bediuzzaman's concept of tolerance as a pillar of wasatiyyah (moderation) and unity - Ahmad H.Osman, Rahmah (The Journal of Risale-i Nur Studies, 2018)
The Imam Badi’uzzaman was a contemporary Turkish scholar who lived in the period of the late 19th early 20th century. This period is world history had a profound impact on the religious as well as international landscape both in Turkey and internationally. The Imam living in this era with all its changes and challenges for the Muslim community particularly is an extraordinary balm, and workable, implementable solution for the internal conflicts and tension within the Muslim community as well as a vehicle of understanding between other communities. This paper thus investigates tolerance and wasatiyyah (moderation) in the life, legacy as well as the writings of the Imam to ensure that nether are taken in a vacuum and get a holistic picture of the ideas as presented by the imam, in the writings of Risale-i Nur, the legacy of Talib-i Nur. It firstly explores the imam’s well documented bibliography in the on the old Said and new Said periods. It explores the imam’s attitude to acquiring and reforming knowledge in the form of his own knowledge acquisition and the conceptualization of Medresetü’z-Zehrâ, his interaction with government and politics to his stance of being apolitical, his interaction with non-Muslims and the adaptation of the printing of Risale-I Nur. The concept of tolerance in the thoughts and scholarship of the Imam covers tolerance between the Talib-i Nur, Muslim tolerance with each other, of which the main concepts being sincerity, desire for your brother’s greatness, work together for a common purpose, and Shia Sunni relations where he highlights the dispute as being “meaningless, disloyal, unjust, and harmful”, as well as the relations with non-Muslims like the Christians and Zoroastrians highlighting the scenarios of Muslims as a majority and as a minority. The pillars of tolerance, faith and forgiveness are also explored. In the legacy and implementation of the Imam’s teachings the Talib-i Nur in the form of Hayrat Foundation is highlighted. The imam has a comprehensive workable system which if explored thoroughly can be implemented to assist a substantial amount of issues between different groups of the Muslim community.